Natural and Synthetic Flavylium Derivatives: Isolation/Synthesis, Characterization and Application - Diana-Ionela Dăescu; Iulia Păușescu; Ioana Cristina Benea; Francisc Peter; Anamaria Todea; Federico Zappaterra; Andreea Anda Alexa; Alina Ramona Buzatu (Molecules)
Given the natural origins of flavylium derivatives, their chemical modifications, and their large potential uses in food, medicine, or green chemistry, the present review is a comprehensive study of flavylium-derived compounds. Several topics such as the green extraction and isolation techniques of flavylium derivatives including their chemical modifications and various characterization tools such as NMR, HPLC, and mass spectrometry are discussed in the review. Furthermore, the use of these derivatives in medicine, food, and materials science is presented, highlighting their relevance and the need for further investigation. Therefore, by examining the advantages and disadvantages of natural and synthetic sources, the review asserts the increased relevance of flavylium-based compounds in active molecules.